Analysis of the Planetary Pressures-adjusted Human Development Index (PHDI) - Sherly Kristyana Putri; Fithriyah (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: This paper empirically examines the influence of health, education, income, and environmental pressures on the planetary pressures-adjusted human development index (PHDI), providing an overview of sustainable development quality within a broader macroeconomic context. Design/Methods/Approach: Time-series data covering the period 1990-2023 are employed, using econometric regression techniques to assess the effects of life expectancy (LE), mean years of schooling (MYS), gross domestic product (GDP), carbon emissions (CE), and material footprint per capita (MF) on PHDI. The data are obtained from authoritative sources, including the UNDP Human Development Reports, GlobalData, and the World Development Indicators (World Bank). Purposive sampling is applied to capture key socio-economic and environmental indicators relevant to sustainable development. Findings: The findings demonstrate that LE, MYS, and GDP exert positive and statistically significant influences on PHDI, highlighting the essential contributions of health, extended education, and economic growth in fostering sustainable human development. Conversely, CE and MF exhibit no notable impact. However, the negative coefficients associated with CE and MF indicate possible environmental hazards if left unmitigated. The findings emphasize that although economic and social advancement is crucial, environmental considerations must not be overlooked in development planning. Originality/Value: The contribution of this paper lies in integrating environmental pressure indicators carbon emissions and material footprint into a national-level analysis of human development, thereby offering a more comprehensive macroeconomic perspective beyond conventional HDI components or regional income-based assessment. Practical/Policy implication: The findings indicate that policymakers ought to prioritize investments in health, equitable education quality, and inclusive economic growth, while also enhancing environmental policies, promoting resource efficiency, and supporting renewable energy initiatives to achieve long-term sustainable development.